2006
DOI: 10.1227/01.neu.0000197490.60670.a8
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted Quantification of Occlusion and Coil Densities on Angiographic and Histological Images of Experimental Aneurysms

Abstract: Computer-assisted DSA evaluation, delivering more precise values than subjectively estimated occlusion, may be a useful tool for follow-up studies. Comparing computer-assisted angiographic with histometrical occlusion demonstrates limits of DSA in displaying the real morphology of coil-embolized aneurysms. The clinically postulated correlation of OR and coil densities was statistically corroborated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
(16 reference statements)
1
21
0
Order By: Relevance
“…In experimental aneurysms, the theoretic benefits of computerized angiographic occlusion rating have already been shown. 14 Comparable with the findings of the above-cited experimental study, also in the present human aneurysmal series, 12 of 14 aneurysms showed lower computerized OR values compared with subjective angiographic estimations. Besides several methodologic factors listed in the limitation section below, a major reason for this tendency to lower computerized angiographic OR values seems to be the higher-resolution power of the computerized gray value definition of the contrast medium in the parent arteries.…”
Section: Comparison Of Computerized Angiographic Occlusion Rates Withsupporting
confidence: 90%
See 2 more Smart Citations
“…In experimental aneurysms, the theoretic benefits of computerized angiographic occlusion rating have already been shown. 14 Comparable with the findings of the above-cited experimental study, also in the present human aneurysmal series, 12 of 14 aneurysms showed lower computerized OR values compared with subjective angiographic estimations. Besides several methodologic factors listed in the limitation section below, a major reason for this tendency to lower computerized angiographic OR values seems to be the higher-resolution power of the computerized gray value definition of the contrast medium in the parent arteries.…”
Section: Comparison Of Computerized Angiographic Occlusion Rates Withsupporting
confidence: 90%
“…In our study, this validation was aimed by the comparison of the new computerized angiographic methods with the reference of corresponding histologic ground sections of the aneurysms, displaying the intra-aneurysmal morphologic detail with the highest available resolution power for morphometric quantification. [13][14][15]22 The comparison of computerized and histometric occlusion rates in the present series did not result in a statistically significant difference (P ϭ .2163) and showed, indeed, a very good correlation (r ϭ 0.799; P Ͻ .001) of computerized angiographic occlusion rating with good statistical power, despite the small sample size of 14 aneurysms.…”
Section: Comparison Of Computerized Angiographic Occlusion Rates Withmentioning
confidence: 43%
See 1 more Smart Citation
“…2 Thus, experimental animal studies are crucial to test new and better endovascular devices, to improve long-term aneurysm occlusion. [3][4][5] The choice of the model is essential for the comparability of experimental findings with human conditions. 6 In a comparison of the currently used animal models in rats, rabbits, canines, and swine, [7][8][9] the rabbit model showed advantageous comparability with the human coagulation system and the best cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, it has already been shown that the foreign body response to the monofilament sutures around the anastomosis is only benign and that this chronic inflammatory reaction to nonresorbable sutures is locally confined to the outer parts of the respective vessel walls. 5,22 What is more, the aneurysm wall in the venous pouch arterial bifurcation model consists of an unaltered vein transplant with just a few elastic membranes. These features can also be seen in human intracranial aneurysm walls.…”
Section: Discussionmentioning
confidence: 99%